Analysis of Rare Earth Elements in Uranium Using Handheld Laser-Induced Breakdown Spectroscopy (HH LIBS). Issue 11 (November 2018) - Manard, Benjamin T.; Wylie, E. Miller; Willson, Stephen P.
A portable handheld laser-induced breakdown spectroscopy (HH LIBS) instrument was evaluated as a rapid method to qualitatively analyze rare earth elements in a uranium oxide matrix. This research is motivated by the need for development of a method to perform rapid, at-line chemical analysis in a nuclear facility, particularly to provide a rapid first pass analysis to determine if additional actions or measurements are warranted. This will result in the minimization of handling and transport of radiological and nuclear material and subsequent exposure to their associated hazards. In this work, rare earth elements (Eu, Nd, and Yb) were quantitatively spiked into a uranium oxide powder and analyzed by the HH LIBS instrumentation. This method demonstrates the ability to rapidly identify elemental constituents in sub-percent levels in a uranium matrix. Preliminary limits of detection (LODs) were determined with values on the order of hundredths of a percent. Validity of this methodology was explored by employing a National Institute of Standards and Technology (NIST) standard reference materials (SRM) 610 and 612 (Trace Elements in Glass). It was determined that the HH LIBS method was able to clearly discern the rare earths elements of interest in the glass or uranium matrices.